A Fantasy in Fashion: African American Empowerment in an Era of Opulence - Carter-David, Siobhan; Wu, Ellen (Race and Retail: Consumption across the Color Line, 2015)
Race has long shaped shopping experiences for many Americans. Retail exchanges and establishments have made headlines as flashpoints for conflict not only between blacks and whites, but also between whites, Mexicans, Asian Americans, and a wide variety of other ethnic groups, who have at times found themselves unwelcome at white-owned businesses. Race and Retail documents the extent to which retail establishments, both past and present, have often catered to specific ethnic and racial groups. Using an interdisciplinary approach, the original essays collected here explore selling and buying practices of nonwhite populations around the world and the barriers that shape these habits, such as racial discrimination, food deserts, and gentrification. The contributors highlight more contemporary issues by raising questions about how race informs business owners’ ideas about consumer demand, resulting in substandard quality and higher prices for minorities than in predominantly white neighborhoods. In a wide-ranging exploration of the subject, they also address revitalization and gentrification in South Korean and Latino neighborhoods in California, Arab and Turkish coffeehouses and hookah lounges in South Paterson, New Jersey, and tourist capoeira consumption in Brazil. Race and Retail illuminates the complex play of forces at work in racialized retail markets and the everyday impact of those forces on minority consumers. The essays demonstrate how past practice remains in force in subtle and not-so-subtle ways.
Keywords: dept.his

An Academy at the Court of the Tsars: Greek Scholars and Jesuit Education in Early Modern Russia - Chrissidis, Nikolaos A. (NIU Press, 2015)
Keywords: 17th century; 17th century; Education; Higher; 17th century; Greeks; Education; History; History; Jesuits; Leichoudēs; Iōannikios; 1633-1717; Leichoudēs; Sōphronios; 1652-1730; Moskovskai︠a︡ slavi︠a︡no-greko-latinskai︠a︡ akademii︠a︡; Moscow; Russia; Russia (Federation); dept.his; faculty_collection

Our Land, Our Life, Our Future: Black South African Challenges to Territorial Segregation, 1913-1948 - Feinberg, Harvey M. (Unisa Press, 2015)
Keywords: 1909-1961; History; History; South Africa; Land reform; Law and legislation; South Africa; dept.his; faculty_collection

Major Problems in American Indian History: Documents and Essays - Hurtado, Albert L.; Iverson, Peter; Bauer, William J.; Amerman, Stephen Kent (Cengage Learning, 2015)
Keywords: History; History; Indians of North America; Indians of North America; Sources; dept.his; faculty_collection

Mapping and Charting in Early Modern England and France: Power, Patronage, and Production - Petto, Christine Marie (Lexington Books, 2015)
Keywords: Cartography; England; France; History; History; Cartography; History; Map industry and trade; Paris; dept.his; faculty_collection

Vietnamese Traditional Medicine: A Social History - Thompson, Claudia Michele (NUS Press, 2015)
SCSU Faculty Scholar Award
Keywords: History; Medicine; Chinese; History; Vietnam; Medicine; Traditional; SCSU Faculty Scholar Award; Vietnam; award_winner; dept.his; faculty_collection; history; Medicine; Chinese Traditional; history; Smallpox; prevention & control; Traditional medicine

Greeks in seventeenth-century Russia - Chrissidis, N.A. (Portraits of Old Russia: Imagined Lives of Ordinary People, 1300-1745, 2015)
Journal Abbreviation: Portraits of Old Russ.: Imagined Lives of Ordinary People, 1300-1745
Keywords: dept.his

Performing Politics - Paddock, Troy R. E. (Contemporary Aesthetics, 2015)
Walter Benjamin’s observation that fascism turns politics into aesthetics is, by now, a well-worn idea. This article argues that Benjamin’s critique of politics can apply just as much to the modern democratic politics of the United States. Borrowing from Benjamin, Jürgen Habermas, and Carl Schmitt, this article suggests that modern political discourse in the United States does not follow the classical liberal ideal of rational discourse in the marketplace of ideas within the public sphere. Instead, contemporary politics has become spectacle where images and slogans replace thought and debate in a 24/7 news cycle and political infotainment programs. The result is that progressives and conservatives have their own political “ecospheres” which enable them to have their own perspective reinforced, and debate is replaced by straw man arguments and personal attacks.
Keywords: dept.his; ⛔ No DOI found

’We Here Highly Resolve’: The End of Compromise and the Return of Revolutionary Time - Forbes, Robert Pierce (Conceived in Liberty: Perspectives on Lincoln at Gettysburg, 2015)
Keywords: dept.his

The World of Eastern Orthodoxy - Chrissidis, Nikolaos A. (The Oxford Handbook of Early Modern European History, 1350-1750, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Citation Key Alias: lens.org/025-896-017-121-207
Keywords: dept.his

Book Review: Mohammad rihan: the politics and culture of an umayyad tribe: conflict and factionalism in the early islamic period . viii, 231 pp. london and new york: I.B. tauris, 2014. £58. ISBN 978 1 78076 564 8. - Judd, Steven (Bulletin of The School of Oriental and African Studies-university of London, 2015)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/169-875-883-163-154 tex.type: [object Object]
Keywords: book.review; dept.his